Fjölskylduljósmyndir. Birtingarmynd einstaklinga í umhverfi sínu - Guðrún Sv. Guðmundsdóttir 1975- (2011)
When marketing Iceland and its people nature has been at the forefront, with it being portrayed as “untouchable” or “clean”. This thesis criticises the power that consists in the creation of a stereotypical image of the country and its nation and on how the academic debate has been confined to that stereotype, strengthening it further. The presentation of nature in family albums from Bolungarvík is analysed and compared to the stereotypical image that has been portrayed of Iceland and Icelanders for tourism promotion. The research is mainly based on qualitative research methods. The key data comes from a participant observation, along with interviews, and thorough inspection of family albums. Other data was also used, such as public reports, newspaper articles etc. When evaluating the data a special emphasis was placed on the presentation of nature, more specifically on which environmental aspects are portrayed in family albums and which are not. The analysis tries to shed a light on why some environmental aspects are visible, while others are almost invisible. The research findings indicate a difference between the way nature is portrayed in family albums on one hand and in photographs for tourism promotion on the other hand. In family albums the nature is not shown as being “clean” or “untouched”, but rather as a part of people’s experiences, their society and its environment. The findings also imply that those environmental aspects which people feel threatened by do not appear in family albums and that a certain distance to nature’s threats is needed so that its beauty can be enjoyed. Í markaðssetningu á landi og þjóð hefur náttúran verið miðlæg, hún sett fram sem „ósnert“ eða „hrein“. Verkefnið er liður í gagnrýni á það vald sem felst í staðalmyndarsköpun af landi og þjóð og hvernig umræða fræðimanna hefur einskorðast við þessa staðalmynd og fest hana enn frekar í sessi. Skoðuð er birtingarmynd náttúrunnar á fjölskylduljósmyndum frá Bolungarvík og hún borin saman við þá staðalímynd sem dregin hefur verið ...